Plasma SARS-CoV-2 RNA Levels as a Biomarker of Lower Respiratory Tract SARS-CoV-2 Infection in Critically Ill Patients With COVID-19. (2nd May 2022) - Jacobs, Jana L; Naqvi, Asma; Shah, Faraaz A; Boltz, Valerie F; Kearney, Mary F; McVerry, Bryan J; Ray, Prabir; Schaefer, Caitlin; Fitzpatrick, Meghan; Methé, Barbara; Lee, Janet S; Morris, Alison; et al.
Abstract: Plasma SARS-CoV-2 viral RNA (vRNA) levels are predictive of COVID-19 outcomes in hospitalized patients, but whether plasma vRNA reflects lower respiratory tract (LRT) vRNA levels is unclear. We compared plasma and LRT vRNA levels in serially collected samples from mechanically ventilated patients with COVID-19. LRT and plasma vRNA levels were strongly correlated at first sampling (n = 33, r = 0.83, P < 10 −9 ) and then declined in parallel in available serial samples except in nonsurvivors who exhibited delayed vRNA clearance in LRT samples. Plasma vRNA measurement may offer a practical surrogate of LRT vRNA burden in critically ill patients, especially early after ICU admission. Abstract : Lower respiratory tract (LRT) and plasma viral RNA (vRNA) levels are strongly correlated in mechanically ventilated COVID-19 patients. There is delayed LRT vRNA clearance in nonsurvivors. Plasma vRNA may offer a practical surrogate of LRT vRNA early in critical illness.